European mtDNA Variants Are Associated With Differential Responses to Cisplatin, an Anticancer Drug: Implications for Drug Resistance and Side Effects - Patel, Tej H.; Norman, Lucas; Chang, Steven; Abedi, Sina; Liu, Catherine; Chwa, Marilyn; Atilano, Shari R.; Thaker, Kunal; Lu, Stephanie; Jazwinski, S. Michal; Miceli, Michael V.; Udar, Nitin; et al. (Frontiers in Oncology, 2019)
Background: Cisplatin, a powerful antitumor agent, causes formation of DNA adducts and activation of apoptotic pathways. Presently, cisplatin resistance develops in up to 70% of patients but the underlying molecular mechanism(s) are unclear and there are no markers to determine which patients will become resistant. Mitochondria play a significant role not only in energy metabolism but also retrograde signaling (mitochondria to nucleus) that modulates inflammation, complement, and apoptosis pathways. Maternally inherited mitochondrial (mt) DNA can be classified into haplogroups representing different ethnic populations that have diverse susceptibilities to diseases and medications. Methods: Transmitochondrial cybrids, where all cell lines possess identical nuclear genomes but either the H (Southern European) or J (Northern European) mtDNA haplogroups, were treated with cisplatin and analyzed for differential responses related to viability, oxidative stress and expression levels of genes associated with cancer, cisplatin-induced nephrotoxicity and resistance and TP53), apoptosis and signaling pathways. Results: The cisplatin-treated-J cybrids showed greater loss of cell viability along with lower levels of reactive oxygen species and mitochondrial membrane potential compared to cisplatin-treated-H cybrids. After cisplatin treatment, J cybrids showed increased gene expression of BAX, CASP3 and CYP51A, but lower levels of SFRP1 compared to untreated-J cybrids. The cisplatin-treated-H cybrids had elevated expression of CDKN1A/P21, which has a role in cisplatin toxicity, compared to untreated-H cybrids. The cisplatin-treated H had higher transcription levels of ABCC1, DHRS2/HEP27 and EFEMP1 compared to cisplatin-treated-J cybrids. Conclusions: Cybrid cell lines that contain identical nuclei but either H mtDNA mitochondria or J mtDNA mitochondria respond differently to cisplatin treatments suggesting involvement of the retrograde signaling (from mitochondria to nucleus) in the drug-induced cell death. Varying toxicities and transcription levels of the H versus J cybrids after cisplatin treatment support the hypothesis that mtDNA variants play a role in the expression of genes affecting resistance and side effects of cisplatin.